Treaties to prevent double taxation and their impact on the right to private property rights in latin american states of the Organization for Economic Cooperation and Development (OECD) - Salazar Urbina, Daniel Stefano (DIXI, 2024)
The present research aims to determine that the Double Taxation Avoidance Agreements impact the protection of property rights in the Latin American states of the Organization for Economic Cooperation and Development (oecd). The methodology employed includes a quantitative approach, correlational level, basic type, non-experimental design, deductive method, and a sample composed of thirty international tax law professionals (non-probabilistic sampling design), as well as the questionnaire as the data collection instrument. It is concluded that the Double Taxation Avoidance Agreements significantly impact the protection of property rights in the Latin American states of the oecd. This is because the signing of these tax treaties, both by full-fledged member states (Chile, Colombia, Costa Rica, and Mexico) and by those invited to initiate their accession process (Brazil and Peru), aims intrinsically to prevent situations of double taxation that lead to assumptions of confiscation and, therefore, towards violations of property rights.